2004
DOI: 10.1097/01.phm.0000146503.25221.1d
|View full text |Cite
|
Sign up to set email alerts
|

Measuring High-Level Mobility After Traumatic Brain Injury

Abstract: High-level mobility is important for participation in many pre-accident activities after traumatic brain injury (TBI). This review examined which measures are used to quantify physical status and mobility after TBI to determine their appropriateness for measuring high-level mobility. Electronic databases, hand searching of several TBI journals, and citation tracking from retrieved articles were used to identify all TBI outcome studies from 1990 through to May 2004. Preliminary screening identified articles tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 152 publications
1
30
0
Order By: Relevance
“…Published TBI outcome studies are skewed toward global measures and/ or measures within the behavioral and cognitive rather than physical domains. A recent literature review of all TBI outcome studies from 1990 to 2004 by Williams et al found only 175 articles that reported on mobility or physical outcome after TBI [6]. In virtually all of these studies, the mobility and physical domains were assessed by functional or disability instruments, without the inclusion of impairment measures.…”
Section: Introductionmentioning
confidence: 99%
“…Published TBI outcome studies are skewed toward global measures and/ or measures within the behavioral and cognitive rather than physical domains. A recent literature review of all TBI outcome studies from 1990 to 2004 by Williams et al found only 175 articles that reported on mobility or physical outcome after TBI [6]. In virtually all of these studies, the mobility and physical domains were assessed by functional or disability instruments, without the inclusion of impairment measures.…”
Section: Introductionmentioning
confidence: 99%
“…Standardized functional measures commonly used in TBI rehabilitation, such as the Functional Independence Measure (FIM), do not specifically assess balance [7]. Quantitative tests to assess balance that have been described for the TBI population include variations of the Romberg test [8], the test of sway [9], the Berg Balance Scale [10], and other more subjective tests.…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of mobility following acquired brain injury (ABI) and particularly traumatic brain injury (TBI) has primarily focused on motor performance during the inpatient stage of movement rehabilitation [1]. There has been little attempt to quantify higher levels of mobility, such as running, jumping and hopping in the post-acute phase.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, existing scales used in neurological rehabilitation are not able to quantify mobility at the level required for participation in physically demanding employment roles, leisure activities, social roles and sporting activities [1]. The High-level Mobility Assessment Tool (HiMAT) was developed to quantify high-level mobility outcomes following TBI [13,14].…”
Section: Introductionmentioning
confidence: 99%